Effects of a home care program in geriatrics on the number of hospitalizations and emergency room visits (2021)
Objective: To evaluate the effects of the home care program of the Intellectus Center of Memory and Cognition in a group of multimorbid and dependent patients with regards to the number of hospitalizations and emergency room visits, before the program and